Dynamic B0 shimming for multiband imaging using high order spherical harmonic shims. Issue 1 (28th August 2020) - Hetherington, Hoby P.; Moon, Chan Hong; Schwerter, Michael; Shah, Nadim Joni; Pan, Jullie W.
Abstract : Purpose: To describe and implement a strategy for dynamic slice‐by‐slice and multiband B0 shimming using spherical harmonic shims in the human brain at 7T. Theory: For thin axial slices, spherical harmonic shims can be divided into pairs of shims (z‐degenerate and non‐z‐degenerate) that are spatially degenerate, such that only ½ of the shims (non‐z‐degenerate) are required for single slice optimizations. However, when combined, the pairs of shims can be used to simultaneously generate the same in‐plane symmetries but with different amplitudes as a function of their z location. This enables multiband shimming equivalent to that achievable by single slice‐by‐slice optimization. Methods: All data were acquired at 7T using a spherical harmonic shim insert enabling shimming up through 4th order with two additional 5th order shims (1st‐4th+). Dynamic shim updating was achieved using a 10A shim power supply with 2 ms ramps and constrained optimizations to minimize eddy currents. Results: In groups of eight subjects, we demonstrated that: 1) dynamic updating using 1st‐4th+ order shims reduced the SD of the B0 field over the whole brain from 32.4 ± 2.6 and 24.9 ± 2 Hz with 1st‐2nd and 1st‐4th+ static global shimming to 15.1 ± 1.7 Hz; 2) near equivalent performance was achieved when dynamically updating only the non‐z‐degenerate shims (14.3 ± 1.5 Hz), or when a using multiband shim factor of 2, MBs = 2, and all shims (14.4 ± 2.0 Hz). Conclusion: High order spherical harmonics provide substantial improvements over static global shimming and enable dynamic multiband shimming with near equivalent performance to that of dynamic slice‐by‐slice shimming. This reduces distortion in echo planar imaging.